Mediterranean evergreen oak diversity: morphological and chemical variation of acorns - Afzal-Rafii, Zara; Dodd, Richard S.; Pelleau, Yvonne (Canadian Journal of Botany, 1992)
Acorns of mediterranean evergreen oak were collected from eight ecogeographically contrasting localities in Italy and Spain. Biometrical analysis of acorns and their cupules showed much greater variation among Spanish populations, encompassing the variation in Italy. The Spanish population at El Pardo, considered the type locality for Quercus rotundifolia, separated from all others. Multivariate analyses of the chemical data indicated, on the one hand, separation of Spain from Italy, and on the other hand, a separation of interior Spanish populations from coastal populations. The importance of lipid composition in the former separation may reflect genetic differentiation between these two origins. Coastal populations were closer to Italian and we suggest were a zone of introgression and hybridization between Quercus ilex and Q. rotundifolia and probably also Quercus coccifera at Bonete Albacete
doi: 10.1139/b92-184doi: 10.1139/b92-184The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: biometry; chemistry; diversity; ecogeography; Quercus ilex; Quercus rotundifolia